DIGITALISASI DAN ASPEK KEUANGAN DALAM PENGEMBANGAN UMKM DI ERA DIGITAL: TINJAUAN LITERATUR - Khaira, Imamul; Wisnu Rayhan Adhitya; Syati Manaharawan siregar; Tiara Reizsa Adhitya; Evi Syuriani Harahap (Universitas Haji Sumatera Utara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in a country's economy. In the digital era, digital transformation is a necessity to enhance MSME competitiveness and sustainability. However, this digitalization process is inseparable from the aspects of healthy and effective financial management. This research aims to review the latest literature on the interaction between digitalization and financial aspects in the context of MSME development in the digital era. Using a systematic literature review (SLR) method based on 12 provided scholarly articles, this research synthesizes findings related to the urgency of digitalization, its challenges and benefits, the importance of financial literacy and financial inclusion, the digitalization of financial processes, and their impact on MSME performance and sustainability. The review results indicate that digitalization not only includes digital marketing but also the digitalization of financial processes such as bookkeeping and reporting. Financial literacy and financial inclusion are very important in supporting the adoption of financial technology (fintech) and good financial management practices in the digital era. Various studies confirm the positive influence of digitalization and financial aspects on MSME performance and sustainability, although challenges such as limited infrastructure, digital literacy, and resistance to change still persist. Support from the government and other stakeholders through training and providing access to technology plays an important role in facilitating the digital transition and strengthening the financial aspects of MSMEs. This review provides insights for MSME actors, policymakers, and researchers regarding critical areas that require further attention to support MSME development in the digital era.